Impacto de LoRaWAN no Desempenho de Plataformas de IoT baseadas em Nuvem e Névoa Computacional - Zyrianoff, Ivan; Heideker, Alexandre; Silva, Dener Ottolini; Kleinschmidt, João Henrique; Kamienski, Carlos Alberto (Anais do Workshop em Clouds e Aplicações (WCGA), 2019)
LoRaWAN is a new technology that has been consolidating as a key data communication component to send data in IoT-based systems, due to its ability to send data over long distances with low energy costs. However, literature considers only wireless aspects, disregarding its computational aspects and its integration with IoT platforms, as well as ignoring the deployment possibilities that involve cloud and fog computing. In order to understand the computational impacts of the LoRa architecture we performed a careful performance evaluation study in a complex IoT scenario, exploring cloud and fog computing scenarios and integrating with the IoT FIWARE platform. The results show that the LoRaWAN architecture is scalable, but it has impacts on system performance.